Patient Satisfaction with Clear Aligners vs. Traditional Braces: A Comparative Study - AbdulMajeed AlMogbel (Journal of Pharmacy and Bioallied Sciences)
Background: Clear aligners and traditional braces are two popular orthodontic treatments, each offering unique benefits. While clear aligners emphasize aesthetics and comfort, traditional braces are considered effective for complex dental cases. This study aimed to compare patient satisfaction levels between these two treatment modalities. Materials and Methods: A total of 100 orthodontic patients were recruited, with 50 undergoing treatment with clear aligners and 50 with traditional braces. Patient satisfaction was assessed using a validated questionnaire covering aspects such as aesthetics, comfort, speech interference, ease of maintenance, and overall satisfaction. Data were collected at 6 months and 12 months post-treatment initiation. Statistical analysis was conducted using the Chi-square test and independent t-test, with a significance level set at P < 0.05. Results: Patients treated with clear aligners reported higher satisfaction scores in terms of aesthetics (8.7 ± 1.2 vs. 5.4 ± 1.8, P < 0.01) and comfort (8.2 ± 1.5 vs. 4.9 ± 1.6, P < 0.01). Speech interference scores were slightly better for clear aligners (7.8 ± 1.3) compared to traditional braces (6.2 ± 1.5, P < 0.05). However, no significant differences were observed in overall treatment effectiveness between the groups (9.0 ± 1.0 for clear aligners vs. 8.8 ± 1.1 for braces, P > 0.05). Conclusion: Clear aligners demonstrated higher patient satisfaction in terms of aesthetics and comfort compared to traditional braces, making them a preferred choice for patients prioritizing these factors. However, both treatments were equally effective in achieving orthodontic goals, indicating that the choice of modality should consider individual preferences and case complexity.